Managing Liver Cirrhosis: a Multidisciplinary Approach - V. M. Durleshter; S. A. Gabriel; N. V. Korochanskaya; O. V. Kovalevskaya; S. N. Serikova; P. V. Markov; O. A. Usova; D. S. Murashko; V. Yu. Dyn'ko; A. Yu. Bukhtoyarov; M. A. Basenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Analysis of the experience of managing patients with liver cirrhosis (LC) at the Regional Clinical Hospital No. 2 of the Ministry of Health of Krasnodar Krai.Materials and methods. In this retrospective study, we assessed data on routine outpatient monitoring of 832 patients with LC and oesophageal varices by the outpatient and inpatient services of the Regional Clinical Hospital No. 2 during 2009-2019.Results. Endoscopic oesophageal variceal ligation was performed in 832 patients, with total 1149 surgeries and 1 to 8 banding repeats per individual. Transjugular intrahepatic portosystemic shunting (TIPS) was implemented in 2014 and performed 51 times in 5 years, coupled in 20 patients with simultaneous gastric variceal embolisation. Oesophageal variceal ligation preceded TIPS in 34 (66.7 %) patients; 62 patients were included in the liver transplant waiting list. Among 17 liver transplant patients, 6 had oesophageal variceal bleeding in history. Endoscopic ligation was performed in 5, and TIPS — in 3 patients awaiting a transplant. Successful adoption of health telecom technologies in Krasnodar Krai renders high-quality specialised medical aid publically accessible, also in remote regions.Conclusion. A model is presented for providing high-tech specialised assistance to LC patients, which engages a surgeon, a gastroenterologist, an endoscopist, an X-ray physician, an endovascular surgeon and an infectionist. A resident physician should coordinate the multidisciplinary team at the outpatient stage, and a surgeon — upon the patient's admission in case of surgical LC complications.